Exposure to silica and silicosis among tin miners in China: exposure-response analyses and risk assessment. Issue 1 (1st January 2001) - Chen, W; Zhuang, Z; Attfield, M D; Chen, B T; Gao, Pi; Harrison, J C; Fu, C; Chen, J-Q; Wallace, W E
Abstract : OBJECTIVES: To investigate the risk of silicosis among tin miners and to investigate the relation between silicosis and cumulative exposure to dust (Chinese total dust and respirable crystalline silica dust). METHODS: A cohort study of 3010 miners exposed to silica dust and employed for at least 1 year during 1960–5 in any of four Chinese tin mines was conducted. Historical total dust data from China were used to create a job exposure matrix for facility, job title, and calendar year. The total dust exposure data from China were converted to estimates of exposure to respirable crystalline silica for comparison with findings from other epidemiological studies of silicosis. Each worker's work history was abstracted from the complete employment records in mine files. Diagnoses of silicosis were based on 1986 Chinese pneumoconiosis Roentgen diagnostic criteria, which classified silicosis as stages I-III—similar to an International Labour Organisation (ILO) classification of 1/1 or greater. RESULTS: There were 1015 (33.7%) miners identified with silicosis, who had a mean age of 48.3 years, with a mean of 21.3 years after first exposure (equivalent to 11.0 net years in a dusty job). Among those who had silicosis, 684 miners (67.4%) developed silicosis after exposure ended (a mean of 3.7 years after). The risk of silicosis was strongly related to cumulative exposure to silica dust and was well fitted by the Weibull distribution, with the risk of silicosis less than 0.1% when the Chinese measure of cumulative exposure to total dust (CTD) was under 10 mg/m 3 -years (or 0.36 mg/m 3 -years of respirable crystalline silica), increasing to 68.7% when CTD exposure was 150 mg/m 3 -years (or 5.4 mg/m 3 -years of respirable crystalline silica). Latency period was not correlated to the risk of silicosis or cumulative dose of exposure. This study predicts about a 36% cumulative risk of silicosis for a 45 year lifetime exposure to these tin mine dusts at the CTD exposure standard of 2 mg/m 3, and a 55% risk at 45 years exposure to the current United States Occupational Safety and Health Administration and Mine Safety and Health Administration standards of 0.1 mg/m 3 100% respirable crystalline silica dust. CONCLUSIONS: A clear exposure-response relation was detected for silicosis in Chinese tin miners. The study results were similar to most, but not all, findings from other large scale exposure-response studies.